Comparison of the diagnostic efficiency for local recurrence of rectal cancer using CT, MRI, PET and PET-CT: A systematic review protocol - Shao, Hongsheng (Medicine (Baltimore), 2018)
BACKGROUND: The risk of local recurrence (LR) continues to threat patients with rectal cancer after surgery or chemoradiotherapy. The main reason is that there is frequently extensive scarring and reactive changes after radiotherapy and resection. Thus, the diagnosis of LR can be challenging. There are different imaging modalities that have been used in the follow-up of rectal cancer, including computed tomography (CT), magnetic resonance imaging (MRI), positron emission tomography (PET), and positron emission tomography-computed tomography (PET-CT) in clinical practice. METHODS: We will systematically search PubMed, EMBASE, the Cochrane Library, and Chinese Biomedical Literature Database for diagnostic trials using CT, MRI, PET, and PET-CT to detect LR of rectal cancer in April, 2018. Two review authors will independently screen titles and abstracts for relevance, assess full texts for inclusion, and carry out data extraction and methodological quality assessment using the QUADAS-2 tool. We will use bivariate meta-analysis to estimate summary sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, and diagnostic odds ratio of CT, MRI, PET, and PET-CT, as well as different sequences of MRI. For each index test, estimates of sensitivity and specificity from each study will be plotted in summary receive operating curve space and forest plots will be constructed for visual examination of variation in test accuracy. We will perform meta-analyses using the hierarchical summary receiver-operating characteristic model to produce summary estimates of sensitivity and specificity. Then, head-to-head and indirect comparison meta-analyses will be carried out. DISCUSSION: This review will help determine the diagnostic accuracy of CT, MRI, PET, and PET-CT for the diagnosis of patients with LR of rectal cancer. ETHICS AND DISSEMINATION: Ethics approval and patient consent are not required, as this study is a systematic review. PROSPERO REGISTRATION NUMBER: CRD42018104918.